Epidemiological Study of Cutaneous Leishmaniasis in Wasit Province - Abdulsada A. Rahi; Zainab K. Hashim; Ali Mohsin Al-Jamea (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study was conducted to detect the cutaneous Leishmaniasis from a total of suspected casesthat were collected from dermatology center of AL-Karamah Teaching Hospital in Al-Kut city from 1stOctober 2019 to the end of February 2020. Totally 60 patients were included 36 males and 24 females. Thecollected skin specimens were smeared and stained with Giemsa stain, then examined by microscope underoil immersion lenses. The results of current study appeared that 56(93.3%) were positive amastigotes, Theprevalence of CL were 36 (60%) in males and 24(40%) in females, while the highest infection 36(60%)in rural area and lowest 24(40%) in urban area. The percent of infection with Cutaneous leishmaniasisaccording to type of lesions recorded were equal in dry and wet ulcers type (50 % ) for each one.